Réponses

2014-10-27T10:50:58+01:00
Bonjour.

a/ Voir graphique.

b/ Graphiquement, on lit x₁ = -3, x₂ = 2, x₃ = 3.
Par le calcul, on pose :
(2 - x) (x² + x - 7) = 4 - x²
(2 - x) (x² + x - 7) = (2 + x) (2 - x)
(2 - x) (x² + x - 7) - (2 + x) (2 - x) = 0
(2 - x) [(x² + x - 7) - (2 + x)] = 0
(2 - x) (x² + x - 7 - 2 - x) = 0
(2 - x) (x² - 9) = 0
(2 - x) (x + 3) (x - 3) = 0
Equation-produit nul a trois facteurs :
3 solutions :
2 - x = 0 ⇔ x = 2
x + 3 = 0 ⇔ x = -3
x - 3 = 0 ⇔ x = 3
S = {-3 ; 2 ; 3}

c/ Voir graphique.

Bonne journee !